Burkina Faso - Public Expenditures Review : Rural Water and Sanitation Sector - World Bank (Washington, DC, 2012)
The review aims at supporting efforts of the government in water and sanitation sector in rural and semi-urban areas. It carries out analysis of sector expenditures evolution during the period 2001-2006 and proposes recommendations likely to help better cope with the current and future challenges. The present review covers only public expenditures of the Ministry of Agriculture, Hydraulics, and Halieutics Resources (MAHRH) to the profit of Rural Water and Sanitation Supply (RWSS). Expenditures of other ministries (education, and health), as well as projects of local development, from Non-Governmental Organization (NGO), and private individuals, for whom data are not available, are excluded. The review of public expenditure in RWSS shows that RWSS sector has experienced dramatic development and that performance in terms of creation of water points is relatively satisfactory during the 2001-2006 periods in Burkina Faso. The annual volume of new water points is about 1.950 points. Facilities realized during this period theoretically made it possible to supply more than three million Burkinabe and the rate of access of populations to drinking water was 60 percent in 2006, according to official sources. RWSS analysis highlights several challenges. These challenges concern primarily: the availability of coherent data, obstacles slowing down the capacity of absorption and negatively affecting efficiency of expenditures, problems related to the sustainability of investments and equipments, huge gap between ambitions and reality on the ground with regard to devolution, decentralization and harmonization of interventions of main technical and financial partners which deserves to be reinforced.